Answer:
3 coefficients in this expression are: -2x, 5y and 9 (natural number)
Step-by-step explanation:
-6x + 5y + 4x + 9
= -6x + 4x + 5y + 9
= -2x + 5y + 9
3 coefficients in this expression are: -2x, 5y and 9 (natural number)
Hope this help you :3
It’s B because I got it right
Answer:
what are the options to the question
Step-by-step explanation:
Doesn't everyone? lol what can I help you with?
Answer:
i4=1
Step-by-step explanation:
Explanation: Rewrite i14 as (i4)3×i2 . If i=√−1, then i2=−1 . From here (i2)2=(−1)2 , so i4=1